Validation of a Methodology for the Detection of Severe Acute Respiratory Syndrome Coronavirus 2 in Saliva by Real-Time Reverse Transcriptase-PCR - Daniel F. Escobar; Pablo Díaz; Diego Díaz-Dinamarca; Rodrigo Puentes; Pedro Alarcón; Bárbara Alarcón; Iván Rodríguez; Ricardo A. Manzo; Daniel A. Soto; Liliana Lamperti; Janepsy Díaz; Heriberto E. García-Escorza; et al. (Frontiers Media S.A., 2021)
In January 2021, the Chilean city of Concepción experienced a second wave of coronavirus 2019 (COVID-19) while in early April 2021, the entire country faced the same situation. This outbreak generated the need to modify and validate a method for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in saliva, thereby expanding the capacity and versatility of testing for COVID-19. This study was conducted in February 2021 in the Chilean city of Concepción during which time, the town was under total quarantine. The study participants were mostly symptomatic (87.4%), not hospitalized, and attended care centers because of their health status rather than being asked by the researchers. People coming to the health center in Concepción to be tested for COVID-19 (via reverse transcriptase polymerase chain reaction [RT-PCR]) from a specimen of nasopharyngeal swab (NPS) were then invited to participate in this study. A total of 131 participants agreed to sign an informed consent and to provide saliva and NPS specimens to validate a method in terms of sensitivity, specificity, and statistical analysis of the cycle threshold (Ct) values from the RT-PCR. Calculations pertaining to the 127 participants who were ultimately included in the analysis showed sensitivity and specificity at 94.34% (95% CI: 84.34-98.82%) and 98.65% (95% CI: 92.70-99.97%), respectively. The saliva specimen showed a performance comparable to NPS as demonstrated by the diagnostic parameters. This RT-PCR method from the saliva specimen is a highly sensitive and specific alternative compared to the reference methodology, which uses the NPS specimen. This modified and validated method is intended for use in the in vitro diagnosis of SARS-CoV-2, which provides health authorities in Chile and local laboratories with a real testing alternative to RT-PCR from NPS.